PENGARUH JEJARING SOSIAL TERHADAP KETAHANAN SOSIAL BUDAYA DI KALANGAN PELAJAR ( STUDI KASUS FACEBOOK DI SMP N 51 JAKARTA) - , Risda Tyas Maharani, Prof. Dr. Ir. Edhi Martono, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Social network is social structure consists of individual or organizational elements. Social network websites are one of the most accessed websites by people through the internet. Facebook is a currently popular social network website. Indonesia holds the second place as the most Facebook user in the world and the first place in Asia. Today, owning a Facebook account is considered a necessity because it is rather difficult to separate it from everyday lives, especially for students. Every student feels the need to own a Facebook account to be considered up to date and associated by their friends. Social network may affect Indonesian society cultural social resilience especially for students. Students are the main aspect of progress in a nation. To understand the influence of Facebook to cultural social resilience then a research was conducted to SMPN 51 Jakarta. Through this research, we obtain the supportive factors of social network utilization, the influence of social network to cultural social resilience, and responses and attitudes toward social network. The research method used here was descriptive analysis by collecting data through questionnaires and interviews. Questionnaires were given with a sample of 10% of population, that is 25 students from VII grade of 248 students, 20 students from VIII grade of 236 students, and 35 students from IX grade of 311 students. Interviews were conducted to the Vice Headmaster of SMPN 51 Jakarta and 5 (five) teachers. Form the result of this research, we obtain the main reason students create Facebook accounts, that is as a communication media. The studentsâ ability to utilize Facebook as a communication, socialization, and study media may be set as a unity facility. The ease in communication and socialization through Facebook can make students accustomed to socializing with anyone and anywhere. By removing the individual behavior in a student and by more prioritizing concern and unity, it could improve Indonesian cultural social resilience. There are no more restrictions due to race, culture, religion in communicating and socializing.